ANALISIS YURIDIS PERBEDAAN ANTARA AKTA PERDAMAIAN YANG DIBUAT OLEH NOTARIS DAN MEDIATOR DALAM KEKUATAN EKSEKUTORIAL - Yudha Prasetyanov (Ensiklopedia Sosial Review, 2025)
Abstract : Conflict is a situation where two or more parties have conflicting interests, goals, or views, and they experience tension or disputes due to these differences, while a dispute occurs between two or more parties when one party feels dissatisfied or harmed. The notarial process, such as the making of a peace deed by a notary, involves the recording of the parties' agreement in the form of an authentic deed. The notary ensures that all legal terms and conditions are met. Mediation, such as the mediation process, involves negotiations and discussions between the parties facilitated by a mediator. Once an agreement is reached, a peace agreement can be drawn up and then authenticated by a notary if necessary. In terms of legal strength, a peace deed made by a notary has stronger legal force and can be used as evidence in court without requiring additional proof. A peace agreement made by a mediator requires notarization to have the same legal force as an authentic deed.Keywords: conflict, peace, notary, mediator.